The effects of household and workplace smoking restrictions on quitting behaviours. Issue 3 (1st September 1999) - Farkas, Arthur J; Gilpin, Elizabeth A; Distefan, Janet M; Pierce, John P
Abstract : OBJECTIVE: To assess the association of household and workplace smoking restrictions with quit attempts, six month cessation, and light smoking. DESIGN: Logistic regressions identified the association of household and workplace smoking restrictions with attempts to quit, six month cessation, and light smoking. SETTING: Large population surveys, United States. SUBJECTS: Respondents (n = 48 584) smoked during the year before interview in 1992–1993, lived with at least one other person, and were either current daily smokers or were former smokers when interviewed. MAIN OUTCOME MEASURES: The outcome measures were an attempt to quit during the last 12 months, cessation for at least six months among those who made an attempt to quit, and light smoking (< 15 cigarettes a day). RESULTS: Smokers who lived (odds ratio (OR) = 3.86; 95% confidence interval (CI) = 3.57 to 4.18) or worked (OR = 1.14; 95% CI = 1.05 to 1.24) under a total smoking ban were more likely to report a quit attempt in the previous year. Among those who made an attempt, those who lived (OR = 1.65, 95% CI = 1.43 to 1.91) or worked (OR = 1.21, 95% CI = 1.003 to 1.45) under a total smoking ban were more likely to be in cessation for at least six months. Current daily smokers who lived (OR = 2.73, 95% CI = 2.46 to 3.04) or worked (OR = 1.53, 95% CI = 1.38 to 1.70) under a total smoking ban were more likely to be light smokers. CONCLUSIONS: Both workplace and household smoking restrictions were associated with higher rates of cessation attempts, lower rates of relapse in smokers who attempt to quit, and higher rates of light smoking among current daily smokers.